The path to the Berlin Wall : critical stages in the history of divided Germany - Wilke, Manfred (Berghahn Books, 2014)
The long path to the Berlin Wall began in 1945, when Josef Stalin instructed the Communist Party to take power in the Soviet occupation zone while the three Western allies secured their areas of influence. When Germany was split into separate states in 1949, Berlin remained divided into four sectors, with West Berlin surrounded by the GDR but lingering as a captivating showcase for Western values and goods. Following a failed Soviet attempt to expel the allies from West Berlin with a blockade in 1948-49, a second crisis ensued from 1958-61.